Classification of postoperative edema based on the anatomic division with mandibular third molar extraction - Yeong Kon Jeong; Jeong-Kui Ku; Sung Hyun Baik; Jae-Seek You; Dae Ho Leem; Sun-Kyu Choi (SpringerOpen, 2021)
Abstract Purpose Several investigations have been performed for a postoperative edema after extraction, but the results have been controversial due to low objectivity or poorly reproducible assessments of the edema. The aim of this study was to suggest a classification and patterns of postoperative edema according to the anatomical division associated with extraction of mandibular third molar as a qualitative evaluation method. Methods This study was conducted forty-four mandibular third molars extracted and MRI was taken within 48 h after extraction. The postoperative edema space was classified by MRI (one anatomic component-buccinator muscle-and four fascial spaces-supra-periosteum space, buccal space, parapharyngeal space, and lingual space), and evaluated independently by two examiners. The inter-examiner reliability was calculated using Kappa statistics. Results The evaluation of buccinator muscle edema showed good agreement and the fascial spaces showed constant high agreement. The incidence of postoperative edema was high in the following order: supra-periosteum space (75.00%), buccinator muscle (68.18%), parapharyngeal space (54.55%), buccal space (40.91%), and lingual space (25.00%). Conclusion Postoperative edema could be assessed clearly by each space, which showed a different tendency between the anatomic and fascial spaces.